Design, synthesis and structural exploration of novel fluorinated dabigatran derivatives as direct thrombin inhibitors - Li, Mei-Lin; Ren, Yu-Jie; Dong, Ming-Hui; Ren, Wei-Xin (European journal of medicinal chemistry, 2015)
Twenty-one fluorinated dabigatran derivatives were designed based on the bioisosteric principle. All derivatives were synthesised and evaluated for their thrombin inhibitory activity in vitro. Among these compounds, 14h, 14m, 14s and 14t were potent and the activity was in the range of reference drug, dabigatran. Three structural changes were introduced in these 21 compounds to elucidate the structure–activity relationship of the drugs. In addition, prodrugs of compounds 14h and 14s were developed to investigate their anticoagulant activities in vivo. In these experiments, compound 16 showed a fairly strong inhibitory effect on thrombin-induced platelet aggregation, and demonstrated potent activity for inhibiting arteriovenous thrombosis with an inhibition rate of (73 ± 6) %, which was comparable to that of dabigatran etexilate (76 ± 2) %. Moreover, molecular docking studies were performed to understand the binding interactions of active compounds 14h, 14s and 14t with thrombin protein (PDB ID:1KTS). Contour maps obtained from the 3D-QSAR model are meaningful in designing more active molecules to act as direct inhibitors of thrombin. [Display omitted] •Twenty-one novel fluorinated dabigatran derivatives were designed and synthesized.•All compounds efficiently inhibited thrombin at nanomolar levels in vitro.•Compound 14s showed the best inhibitory activity against thrombin (IC50 = 3.23 nM).•Compound 16 exhibited a potent inhibition against arteriovenous thrombosis in vivo.•Computational studies were performed to explain the inhibitory mechanism and SAR.